In vitro regeneration and PCR-RAPD based detection of somaclonal variation in kenaf (Hibiscus cannabinus) - Haque, MS; Biswas, T; Islam, MS; Hossain, MS (Progressive Agriculture, 2017)
Though direct systems of regeneration through culture of organized meristems usually produce true-to-type plants, variations in the progenies have widely been reported. Fiber producing kenaf plants (Hibiscus cannabinus L.) were regenerated from petiole, hypocotyls and cotyledonous petiole explants on MS medium containing BAP (benzyl amino purine) and NAA (?-napthaleneacetic acid) followed by assessment of regenerants by RAPD markers to detect somaclonal variation among them. Genomic DNA from twenty seven plants [three mother plants and two clones (clone 1 and 2) from each mother plant with three replications] was subjected to random amplified polymorphic DNA (RAPD) analysis. Fifteen polymorphic loci amplified by three decamer random primers were used to estimate genetic diversity and relatedness in mother plants and their regenerated plantlets. The results showed some degree of polymorphism between mother plants and their regenerated plantlets as well as between regenerated plantlets indicating somaclonal variation among the regenerants. These suggest that the RAPD technique could effectively be used to detect somaclonal variation in H. cannabinus and could be promising for the detection of markers associated with desirable traits. Progressive Agriculture 28 (2): 100-108, 2017